Two-port vitrectomy in the treatment of patients with macular hole - I.A. Frolychev; D.V. Borisova; N.A. Pozdeyeva (Офтальмохирургия)
Purpose. Analysis of the first clinical and functional results of treatment of patients with macular holes using the two-port vitrectomy. Material and methods. An analysis of treatment of 15 patients with a diagnosis of macular hole, operated by the method of two-port vitrectomy, was carried out. According to the Gass classification, 7 patients were diagnosed with stage 3 macular hole, and 8 patients with stage 4. All patients underwent microinvasive vitrectomy according to the developed technique. At the beginning of the operation, two ports were installed – one for the infusion cannula with a built-in illuminator (chandelier), the second for the vitreotome. Next, the epiretinal membrane (ERM) (if any) and the internal limiting membrane (ILM) were removed, and platelet-rich plasma (PRP) was used at the end of the operation. Intra- and postoperative complications were not registered. Results. The maximum period of observation of patients after treatment was 3 months. In all cases, an anatomical result was achieved – complete closure of the macular hole according to optical coherence tomography (OCT). Mean BCVA results 3 months after treatment were 0.32±0.08. In all cases, improvement in visual functions was achieved (p=0.035). Conclusion.The method of two-port vitrectomy in the treatment of macular holes allows to achieve a good anatomical result, improve visual functions, while minimizing surgical trauma.